Si/SiO2@Graphene Superstructures for High‐Performance Lithium‐Ion Batteries. (12th December 2022) - Ma, Yiru; Qu, Huiqi; Wang, Wenna; Yu, Yueqin; Zhang, Xinghao; Li, Bin; Wang, Lei
Abstract: The superstructure composed of various functional building units is promising nanostructure for lithium‐ion batteries (LIBs) anodes with extreme volume change and structure instability, such as silicon‐based materials. Here, a top‐down route to fabricate Si/SiO2 @graphene superstructure is demonstrated through reducing silicalite‐1 with magnesium reduction and depositing carbon layers. The successful formation of superstructure lies on the strong 3D network formed by the bridged‐SiO2 matrix coated around silicon nanoparticles. Furthermore, the mesoporous Si/SiO2 with amorphous bridged SiO2 facilitates the deposition of graphene layers, resulting in excellent structural stability and high ion/electron transport rate. The optimized Si/SiO2 @graphene superstructure anode delivers an outstanding cycling life for ≈1180 mAh g −1 at 2 A g −1 over 500 cycles, excellent rate capability for ≈908 mAh g −1 at 12 A g −1, great areal capacity for ≈7 mAh cm −2 at 0.5 mA cm −2, and extraordinary mechanical stability. A full cell test using LiFePO4 as the cathode manifests a high capacity of 134 mAh g −1 after 290 loops. More notably, a series of technologies disclose that the Si/SiO2 @graphene superstructure electrode can effectively maintain the film between electrode and electrolyte in LIBs. This design of Si/SiO2 @graphene superstructure elucidates a promising potential for commercial application in high‐performance LIBs. Abstract : The elaborately designed anode of Si/SiO2 @graphene superstructure (Si/SiO2 @G‐S) is integrated by 3D‐bridged SiO2 network coated around Si nanoparticles with graphene modification. Benefiting from high tap density, and superior adaptability in expansion generated by the bridged SiO2, the Si/SiO2 @G‐S‐based batteries display superior electrochemical performance and address the key challenges to a certain extent.